2011
DOI: 10.1007/978-3-642-21599-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Trusting to Learn: Trust and Privacy Issues in Serious Games

Abstract: Organizations are increasingly investing in technology-enhanced learning systems to improve their employees' skills. Serious games are one example; the competitive and fun nature of games is supposed to motivate employee participation. But any system that records employee data raises issues of privacy and trust. In this paper, we present a study on privacy and trust implications of serious games in an organizational context. We present findings from 32 interviews with potential end-users of a serious games pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…the receivers) will interpret it. Believing that data portrays individuals in a fair and accurate manner is an important acceptance factor -from a privacy perspective -of technologies and processes that collect personal data (Culnan, 1993;Malheiros et al, 2011). Metzger (2007) investigated the effect of sensitivity on disclosure and found individuals were more likely to withhold items they found more sensitive.…”
Section: Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…the receivers) will interpret it. Believing that data portrays individuals in a fair and accurate manner is an important acceptance factor -from a privacy perspective -of technologies and processes that collect personal data (Culnan, 1993;Malheiros et al, 2011). Metzger (2007) investigated the effect of sensitivity on disclosure and found individuals were more likely to withhold items they found more sensitive.…”
Section: Sensitivitymentioning
confidence: 99%
“…Sensitivity of data is generally considered to be related to privacy perceptions (see Adams and Sasse, 2001 for a privacy model in multimedia communications, or Metzger, 2007 for findings in e-commerce). In a study focused on privacy perceptions in serious games, Malheiros et al (2011) also identified perceived outcome of sharing data as an important factor. The emergence of factors in our thematic analysis which have been identified in studies focused on different types of contexts suggest that the process through which individuals assess data requests may be context-independent, which does not mean the assessments themselves are.…”
Section: Disclosure and Acceptability Of Novel Itemsmentioning
confidence: 99%
“…Another concern is that data is used in a way that harms the individual who disclosed it. The potential negative consequences of a disclosure can make individuals reticent to part with their personal data or make them perceive a data practice as invasive [18] [21] [27].…”
Section: Managing Disclosure Of Personal Datamentioning
confidence: 99%